Effect of COVID-19 crisis on medical students - T., Sasikala; Sahoo, Sibasish; Lakshmanna, N. (International Journal of Research in Medical Sciences, 2020)
COVID-19 pandemic demands and pressures that medical students face mental, physical and spiritual well being can be compromised. Hence this review highlights the beneficial targets to improve mental health in medical students. Collected recent articles from search engines Pub med, Google Scholar, published recently relevant to the COVID-19 pandemic from all over world. Provide routine schedules as much as possible by online services or provide e-services to create new environment, novel consultation and giving time gap in e-assignments, ask them to do the regular exercises may improve the mental health and decrease the stress of the medical students. Hence Avoiding of constant stream of news reports about an outbreak can cause anyone to feel anxious or distressed.